2007
DOI: 10.1097/coc.0b013e31815aff1f
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for Squamous Cell Carcinoma of the Nasal Vestibule

Abstract: RT results in a high cure rate for T1-T2 and favorable T4 tumors. Surgery and RT result in an improved likelihood of cure for patients with extensive T4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0
7

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 7 publications
4
43
0
7
Order By: Relevance
“…In historic series on cohorts treating nasal vestibule tumors with conventional RT or brachytherapy, local control and overall survival rates range from 67% to 92% and 50% to 90%, respectively [2,4,6,14]. The largest series of the DAHANCA study group including 174 patients with nasal vestibule cancer reports a local control rate and an overall survival rate of 67% and 50% at 5 years, respectively [14] (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In historic series on cohorts treating nasal vestibule tumors with conventional RT or brachytherapy, local control and overall survival rates range from 67% to 92% and 50% to 90%, respectively [2,4,6,14]. The largest series of the DAHANCA study group including 174 patients with nasal vestibule cancer reports a local control rate and an overall survival rate of 67% and 50% at 5 years, respectively [14] (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…In the latter series RT was delivered in opposed lateral fields (KV or MV) or with an anterior electron field +/-brachytherapy boost. Doses range from 54 Gy in 3 Gy single doses to 62-69 Gy in 2 Gy or 2.5 Gy doses [2,4,14]. Langendijk et al observed rhinorrhoe in 45%, nasal dryness in 39% and epistaxis in 15% of the patients as late toxicity (4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In these cases, the SCC-NV was expected to be supplied by a branch of the external carotid artery, particularly the facial and internal maxillary arteries. Therefore, RAD-PLAT was indicated [11]. Indeed, angiography showed that the internal maxillary and the facial arteries were supplying the tumor.…”
Section: Discussionmentioning
confidence: 99%